Staff motivation and associated factors in a health district hospital in Benin - Jerome Sossa, Charles; Azandjeme, Colette; Balde, Mamadou S. A.; Soussia, Theodore; Paraiso, Moussiliou N. (International Journal Of Community Medicine And Public Health, 2024)
Background: The aim of this study was to find out about staff motivational related factors at Ouidah’s district hospital in southern Benin. Methods: This was an analytical cross-sectional study involving 108 agents randomly selected with proportional allocation by department. Motivation was measured, as were the intrinsic and extrinsic factors associated with it, using a questionnaire based on a Likert scale. Factors associated with motivation were investigated using the following tests: t-student, ANOVA, post hoc, and logistic regression. Results: The median age of those surveyed was 39 (33.50; 47.50) years, predominantly female (58.30%). Of the staff surveyed, 30.6% had an insufficient level of general motivation. Women were much more motivated by "collaboration" than men (p=0.004). The "achievement" factor was more motivating for staff with university-level education than for those with primary-level education (p=0.001). Those aged between 35 and 50 were less motivated than those under 35 [OR=0.19; 95% CI (0.04; 0.88)]. The opportunity to develop skills at work (p=0.018) and participation in decision-making (p=0.019) were associated with the general level of staff motivation. Reasons for demotivation were dominated by insufficient work materials (24.24%). Conclusions: Staff motivation can be improved through interventions that take into account identified factors.